Efektivitas Program Puskesmas Peduli dan Sayang Lansia dalam Meningkatkan Pelayanan Kesehatan di Puskesmas Desa Suak Ribee Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Mawarni, Melisa; Fadhly, Zuhrizal (Journal of Administration, Governance, and Political Issues, 2025)
This study aims to assess the effectiveness of the Elderly Care and Affection Program in improving healthcare services at the Suak Ribee Village Health Center, Johan Pahlawan District, West Aceh Regency. The program is designed to enhance the well-being of the elderly through early disease detection, health education, and regular monitoring of physical conditions. Employing a descriptive qualitative method, the study involved primary informants including health center personnel and elderly participants. Data were collected through direct observation, in-depth interviews, and documentation, and analyzed systematically through data reduction, data presentation, and conclusion drawing. The findings indicate that the program is effective in providing relevant education, conducting routine health monitoring, and facilitating early identification of health issues. Socialization efforts, including counseling and home visits, have increased elderly awareness of healthy lifestyles and strengthened psychosocial support. The active involvement of families and healthcare workers has also improved interpersonal relationships and reduced social isolation among the elderly. However, challenges persist, particularly in reaching those residing in remote areas with limited service access. Strategic improvements, such as flexible visitation schedules and increased monitoring intensity, are necessary to enhance service coverage. Overall, the program significantly contributes to the physical and psychosocial well-being of the elderly, with broader positive impacts on families and the community.